2017
DOI: 10.1021/acs.jafc.7b01676
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides and Oligosaccharides Produced on Malvar Wines Elaborated with Torulaspora delbrueckii CLI 918 and Saccharomyces cerevisiae CLI 889 Native Yeasts from D.O. “Vinos de Madrid”

Abstract: Polysaccharides and oligosaccharides released into Malvar white wines elaborated through pure, mixed, and sequential cultures with Torulaspora delbrueckii CLI 918 and Saccharomyces cerevisiae CLI 889 native yeasts from D.O. "Vinos de Madrid" were studied. Both fractions from different white wines were separated by high-resolution size-exclusion chromatography. Glycosyl composition and wine polysaccharide linkages were determined by GC-EI-MS chromatography. Molar-mass distributions were determined by SEC-MALLS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Mannoproteins represent the second most abundant group; however, these polysaccharides are formed during alcoholic fermentation or ageing during lees processes [26,47]. Although the first microbiological applications for increasing the content of mannoproteins in wines were based on the use of S. cerevisiae strains, later studies showed that some non-Saccharomyces species release higher concentrations of mannoproteins than S. cerevisiae [47][48][49][50]. Other polysaccharides of a different nature than mannoproteins are also reported for some non-Saccharomyces species [26,[51][52][53].…”
Section: Starmerella Bacillarismentioning
confidence: 99%
“…Mannoproteins represent the second most abundant group; however, these polysaccharides are formed during alcoholic fermentation or ageing during lees processes [26,47]. Although the first microbiological applications for increasing the content of mannoproteins in wines were based on the use of S. cerevisiae strains, later studies showed that some non-Saccharomyces species release higher concentrations of mannoproteins than S. cerevisiae [47][48][49][50]. Other polysaccharides of a different nature than mannoproteins are also reported for some non-Saccharomyces species [26,[51][52][53].…”
Section: Starmerella Bacillarismentioning
confidence: 99%
“…T. delbrueckii was demonstrated to produce lower amounts of acetaldehyde and acetic acid in comparison with S. cerevisiae, confirming its high potential for application in wine production [9,22]. Regarding the production of glycerol, results from the literature are contradictory, showing sometimes higher [9,17,23] and sometimes lower production of glycerol than S. cerevisiae [24]. With respect to organic acids, and apart from acetic acid production, T. delbrueckii also demonstrated a certain activity of malic acid degradation, higher than the usual levels reported for S. cerevisiae [21,22,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…L.) must, produced the highest quantity of pectinases (polygalacturonases) in comparison with other non-Saccharomyces. This pectinase activity of C. stellata CLI 920 could be correlated with the higher galacturonic acid content observed into the oligosaccharides fraction of the wine produced with this strain alone [104]. Also, polygalactosidases enzymes produced by C. stellata together with exo and endoglucosidases are important in the degradation of the β-glucans by Botrytis cinerea [2].…”
Section: Pectinasesmentioning
confidence: 72%
“…Numerous investigations have clearly confirmed that these macromolecules are related to technological and sensorial properties in wines, such as prevention of protein haze in white wines [132], protection against crystallization of tartrate salts [133], interaction with aroma compounds [134], improvement of foam stability and flocculation in sparkling wines [135], reduction of astringency and increased body and mouthfeel [136], and increase of the growth of malolactic bacteria [137]. Moreover, it has been noted that the utilization of Saccharomyces/non-Saccharomyces co-fermentations results in increased release of polysaccharides into the wine, since the high capacity of non-Saccharomyces wine yeasts to release polysaccharides (including mannoproteins) has been verified [104,[138][139][140]. Giovani et al [139] characterized the monosaccharide composition of mannoproteins produced by S. bombicola 3827; they noted that the polysaccharides produced by S. bombicola were essentially mannoproteins with 73-74% of mannose residues.…”
Section: Larger Release Of Polysaccharides (Mannoproteins)mentioning
confidence: 99%